Fluid Volume Detector on a Horizontal Tube Using an Ultrasonic-based Water Level Sensor - Anang Suryana; Paikun; Muchtar Ali Setyo Yudono (Fidelity : Jurnal Teknik Elektro, 2022)
Measurement of the volume of liquid in a vertical cylinder can be done by multiplying the area of the circle with the length of the cylinder. Likewise, measuring the volume of liquid in a horizontal pipe can also be done by multiplying the area by the length of the cylinder. There is a difference between the two measurements of the volume of liquid in the cylinder. In a horizontal cylinder, the measurement of area used is a measurement of the segment of the circle that is exposed to the liquid. To get the value of the circle area segment that is with geometric analysis. In this study, in measuring the volume of liquid in a horizontal cylinder using the multiplication between the circle area segment and the horizontal pipe length. The variables used in measuring the volume of liquid in a horizontal cylinder are, cylinder diameter 2r, liquid level H, and cylinder length L. So that in making this measuring instrument the volume of liquid in a horizontal cylinder has two variables, namely fixed and variable variables. free. For the fixed variables, namely the diameter and length of the cylinder, and for the independent variables, namely the level of the liquid level in the H pipe. In measuring the independent variables, a proximity sensor Type HC-SR04 is used. Installation of a volume measuring device on a horizontal cylinder using a PVC pipe connection type equal tee which is connected to other pipes with the same diameter with a predetermined total length. The fixed variable that has been determined is the cylinder diameter of 10.16 cm with a length of 100 cm.